The Influence of Entrepreneurial Orientation on Business Performance in Culinary MSMEs with the Business Environment as a Mediating Variable - Santoso, Eko; Rahmawati, Desi (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This research aims to describe the influence of entrepreneurial orientation on business performance in culinary MSMEs with the business environment as a mediating variable. The research method that will be used in this research is a descriptive analysis method with a quantitative approach. Data processing in this research uses smartPLS SEM (Partial Least Square - Structural Equation Modeling) software. PLS has the ability to explain the relationship between variables and the ability to carry out analyzes in one test. Hypothesis testing can be seen from the t-statistic value and probability value. Research results the results of testing the first hypothesis are accepted that the Business Environment (Z) influences MSME Business Performance (Y). The results of testing the second hypothesis are accepted that Entrepreneurial Orientation (X) influences MSME Business Performance (Y). The results of testing the third hypothesis are accepted that Entrepreneurial Orientation (X) influences the Business Environment (Z).The results of testing the fourth hypothesis were accepted. Entrepreneurial Orientation (X) has a significant effect on MSME Business Performance (Y). via Business Environment (Z).